Coal consumption-environmental sustainability nexus in developed and developing major coal-consuming economies - Abdulkareem Alhassan; Ilhan Ozturk; Mohammad Fahmi AL-Zyoud; Festus Victor Bekun (Heliyon, 2024)
Coal is crucial for economic progress but equally baneful to the environment. Thus, the coal consumption-environmental sustainability nexus attracted the attention of both policymakers and scholars. This study evaluates the coal consumption-environment nexus in developed and developing countries over the period 2000–2020. We used panel data econometric techniques and the Augmented Anderson–Hsiao (AAH) two-step GMM estimator to assess and compare the impact of coal consumption on CO2. The findings revealed that the consumption of coal aggravates environmental pollution and hinders environmental sustainability. Thus, this study confirms the environment-destroying effect of coal consumption. However, the findings reveal that the negative consequence of coal consumption on the environment is more for the sample of developed countries than that of developing countries. This suggests that coal use harms the environment developed economies than the developing countries. Specifically, we found that the carbon emissions emanating from a one percent (1%) increase in coal consumption of the developed countries is about six-fold more than that of the developing countries. Therefore, this study suggests a gradual phase-out, rather than sudden phase-out, of coal consumption with greater emphasis on developed countries. The implementation of the coal phase-out policy and the removal of fossil fuel subsidies should start with the developed countries or be made more stringent in such countries than the developing economies. The developed countries should relinquish a greater proportion of their coal consumption than the developing countries.